Era Digitalisasi: Membangun Peradaban Baru dalam Kebudayaan Pesantren - Nerisma Eka Putri (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2023)
The presence of digital technology leaps has brought significant changes to religious life in Indonesia, one of which is the scope of Islamic boarding schools. Pesantren at that time became a place for the spread of Islamic teachings that was very massive, with the lecture method carried out in the langgar. The birth of a digital technology system in the world of pesantren can have an impact on the pattern of pesantren education and the pattern of relations between pesantren and society. digital technology is a new civilization created from a series of advances in human thinking from one generation to the next. Pesantren is often considered as an educational institution that is seen classically as a place to study Islam alone. However, it is different from the current situation. Where along with the times, pesantren have undergone a significant transformation, especially in the era of digitalization. This all- digital era has provided updates in social activities and learning systems in pesantren. Therefore, researchers are interested in studying in depth the cult of pesantren with the birth of the digitalization era in the modernization era. This research uses an analytical descriptive approach, this approach is carried out analyzing data based on various phenomena that occur regarding the cult of the pesantren with the birth of the digitalization era in the modernization era and how challenges occur in the digital era in Islamic boarding schools. So that the results found that policy changes in this digital era are an important milestone in pesantren studies, which Yazid mentioned that the pesantren is trying to open itself towards a more transformative and progressive direction, and open to the outside world. So that with the birth of this development, it can help pesantren in facing world civilization in the digital era.